2015
DOI: 10.1371/journal.pone.0127117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Cryptococcal Antigen Lateral Flow Immunoassay in Serum, Cerebrospinal Fluid and Urine for the Diagnosis of Cryptococcosis: A Meta-Analysis and Systematic Review

Abstract: BackgroundA new lateral flow immunoassay (LFA) for the detection of cryptococcal antigen was developed.ObjectiveWe aimed to systematically review all relevant studies to evaluate the diagnostic accuracy of the cryptococcal antigen LFA on serum, CSF and urine specimens.MethodsWe searched public databases including PubMed, Web of Science, Elsevier Science Direct and Cochrane Library for the English-language literature published up to September 2014. We conducted meta-analyses of sensitivity, specificity, positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 18 publications
2
57
0
Order By: Relevance
“…In recent years, improvements in cryptococcal antigen (CrAg) testing with the introduction of lateral flow assays has been a significant development (65). A recent meta-analysis of 12 studies containing 4,622 samples reported the pooled sensitivity and specificity for serum samples at 97.6% and 98.1%, respectively and for CSF at 98.9% and 98.9%, respectively(66). Little data exists related specifically to differences in CrAg validity between different immune states.…”
Section: Diagnostic Approach In Hiv-negative Patients With Cryptococcmentioning
confidence: 99%
“…In recent years, improvements in cryptococcal antigen (CrAg) testing with the introduction of lateral flow assays has been a significant development (65). A recent meta-analysis of 12 studies containing 4,622 samples reported the pooled sensitivity and specificity for serum samples at 97.6% and 98.1%, respectively and for CSF at 98.9% and 98.9%, respectively(66). Little data exists related specifically to differences in CrAg validity between different immune states.…”
Section: Diagnostic Approach In Hiv-negative Patients With Cryptococcmentioning
confidence: 99%
“…In a recent meta-analysis and systematic review [95], a new cryptococcal antigen LFA demonstrated high accuracy in serum and CSF for the diagnosis of cryptococcosis. LFA may eventually be extended to other fungal antigens, since the technology is inexpensive and requires little expertise, but produces accurate results.…”
Section: Fungal Diagnosticsmentioning
confidence: 99%
“…Although the ARUP Laboratories-developed viral PCR assays appeared to be slightly more sensitive than the multiplex panel, we did not directly compare the analytical limits of detection, and the effects of freezethaw cycles may have impacted FA ME sensitivity and/or the abil- ity to confirm previous results. CrAG testing is a highly sensitive and accurate method for diagnosing cryptococcal meningitis (11,12), but we did not have fungal culture results to link to the FA ME and DNA sequence analyses. Furthermore, we did not have access to patient-level information to help adjudicate discrepancies across methods.…”
mentioning
confidence: 99%